Effect of porogenic solvent on selective performance of molecularly imprinted polymer for quercetin - Song,Xingliang (2009)
Molecularly imprinted polymers (MIP's) for quercetin were successfully synthesized by a thermal polymerization method using quercetin as template molecule, acrylamide as functional monomer and ethylene glycol dimethacrylate as cross-linker in the presence of four different porogenic solvents: 1,4-dioxane, tetrahydrofuran (THF), acetone, and acetonitrile. The selective performance of obtained MIP's was evaluated through HPLC analysis. The results indicated that the MIP obtained in THF showed the highest capacity and selectivity. The Scatchard method also supported HPLC results. The results were interpreted by computational quantum chemical analysis through Onsager self-consistent reaction field (SCRF) technique in term of stabilization energy. It was also found that the amount of porogenic solvent used had impact on the adsorption effectiveness of MIP's.